COMPARATIVE ANALYSIS OF LIFE SATISFACTION DETERMINANTS IN RUSSIA AND IN EUROPE - A. V. Andreenkova; N. V. Andreenkova (Дискурс, 2019)
According to European Social Survey (ESS), life satisfaction level in Russia has been constantly increasing during the last decade, but it is still lower than the average European level. To understand the reasons of cross-national differences in life satisfaction, the article analyzes the impact of significant sociodemographic and psychological factors, and also external factors defining the situation and development of society and public institutions that can influence the perception of quality of life. The data shows that the structure of determinants of life satisfaction in Russia is very similar to other European countries. Physical and mental health and financial situation are the most significant factors, as well as the evaluation of general economic and political environment represented by national economy performance and government effectiveness. The impact of financial situation as one of key factors connected to life satisfaction level in Europe is significantly higher than in Russia and these differences have been stable for a number of years. In the middle of 2000s the attitudes to economic and political situation in the country influenced life satisfaction level much stronger than socio-structural factors and personal situation, but in this decade the importance of these factors has decreased and approached European average.